Allosteric properties of PH domains in Arf regulatory proteins. Issue 2 (2nd April 2016) - Roy, Neeladri Sekhar; Yohe, Marielle E.; Randazzo, Paul A.; Gruschus, James M.
ABSTRACT: Pleckstrin Homology (PH) domains bind phospholipids and proteins. They are critical regulatory elements of a number enzymes including guanine nucleotide exchange factors (GEFs) and GTPase-activating proteins (GAPs) for Ras-superfamily guanine nucleotide binding proteins such as ADP-ribosylation factors (Arfs). Recent studies have indicated that many PH domains may bind more than one ligand cooperatively. Here we discuss the molecular basis of PH domain-dependent allosteric behavior of 2 ADP-ribosylation factor exchange factors, Grp1 and Brag2, cooperative binding of ligands to the PH domains of Grp1 and the Arf GTPase-activating protein, ASAP1, and the consequences for activity of the associated catalytic domains.